EFISIENSI, PERSAINGAN, DAN RISIKO DEFAULT PERBANKAN INDONESIA SEBELUM DAN SETELAH PBI 14/26/2012 - Aisha Putrina Sari; Rofikoh Rokhim (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2020)
This study try to find out about the impact of PBI / 14/26/2012 for banks in Indonesia. This regulation limiting the activities of banks based on their core capital. The purpose of this regulation is to improve the efficiency, durability and banking competition. Efficiency is measured by using DEA, endurance proxy by Zscore and competititon proxy by HHI. The results showed that there was a significant difference before and after the regulations issued for variable efficiency and competition but not for durability. The next stage of this research is to know the effect of endurance, competition, regulations and numbers of Board of Directors (BOD) of the efficiency. Measurements were made by a panel regression and stated that the results of the BOD and year significantly affecting efficiency. Keywords: efficiency, competition, default risk, BOD, banking